AN ANALYSIS OF THE NARRATIVE WRITING THE NINTH GRADE STUDENTS OF SMP NEGERI 1 GIANYAR BASED ON TEXT’S COHESION AND COHERENCE - D, ANOM,; K, SEKEN,; W, SUARNAJAYA, (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study aimed at describing and explaining the cohesion and coherence created by the ninth grade students of SMP Negeri 1 Gianyar  in their narrative writings. Another aim was to describe and explain the problems encountered by  students in their narratives. This study used qualitative research which focused on  describing and explaining the coherence and cohesion created by the ninth grade students? in their narrative writings, and the problems encountered by the students. The subject of this study was the ninth grade students of SMP Negeri 1 Gianyar in academic year 2011/2012. The obtained data were in the form of: a) scripts of students narrative writings, b), responses to the students? questionnaire, and c) script of teacher? interview. The main instrument was the researcher himself. The data were analyzed by using the theory introduced by Halliday and Hasan (1976), Alterberg (1987), Wuang, Hui and Sui, Danni, (2010), and Connor (1990) and Connor and John (1990). The findings of the study showed the cohesion of the narratives was achieved by the used of cohesive devices. Grammatical devices included references, substitution, ellipsis and conjunction. And lexical devices included reiteration and collocation. The coherence of the narratives was also achieved through the development of themes, the generic structure, and the tenses used. Most of the students have created cohesive and coherent narratives although some problems identified. They were in sentence patterns, verb patterns or forms, conjunction, spelling, word choice, plural form, over generalization, the use of article, ellipsis, and the use preposition, the use of pronoun, apostrophe, adverb forms, syllabification, and capital letters.